Community Empowerment Based on Circular Economy through the Implementation of Recycling Activities in the Re-Di Program - Niwang Gita Navulani; Andri Nugroho; Catharina Siena; Somaya Saragih; Jiwaning Angger Pamukti (Prospect Publishing, 2026)
The issue of plastic waste management in Indonesia remains a challenge, especially in rural areas that do not yet have an integrated management system. Low sorting rates, limited facilities, and suboptimal utilization of industrial waste worsen the environmental and economic conditions of the community. The Re-Di program, through its recycle activities, serves as a model for community empowerment based on the circular economy to respond to these issues. This paper aims to analyse the implementation process of recycling activities, which include 3R plastic waste management, the development of Batik Javing innovation based on fine polymers, and the use of Oligotrik to support green distribution of MSMEs. The implementation method uses a community-based management, action learning, circular economy, and results-based management approach. The results show that the integration of community-based waste management, appropriate technological innovations, and the sharing of core competencies can strengthen group capacity, build circular value chains, and encourage the transformation of waste into productive resources. The program has had an impact on strengthening community institutions, increasing environmental awareness, and developing the local economy, thereby enriching circular economy-based CSR practices in coastal and rural areas.